Culture of Corporate Social Responsibility (CSR) in India and Turkiye - Nayan Mitra (Cappadocia Journal of Area Studies)
Definitions of Corporate Social Responsibility (CSR) differ from countries and are often aligned to the cultures of a company’s home country. This becomes even more complex under the context of mandated versus voluntary CSR. While compliance guidelines often structure the CSR implementation, but a voluntary CSR helps to mainstream CSR into the governance and sustainability paradigm of the corporation. Therefore, this secondary research seeks to examine the CSR practices of corporations in India and Turkiye and compare them to comprehend their similarities and differences. The two countries have been selected due to their uniqueness - India has been selected as being one of the first countries to have a mandated CSR since April 1, 2014; while Turkiye has been selected due to its geographical distinctiveness. As a first of its kind research, this investigation seeks to contribute significantly to the body of work in the space of CSR and Sustainability study.